Reconstruction of the Regulation on the Validity Period of the Power of Attorney to Charge Mortgage Rights (SKMHT) in MSME Credit to Ensure Legal Certainty - Wibowo, Ihsan Ariyanto; Adonara, Firman Floranta; Soetijono, Iwan Rachmad (Universitas KH. Abdul Chalim Mojokerto, 2026)
The provision of credit to Micro, Small, and Medium Enterprises (MSMEs) often uses a Power of Attorney to Charge Mortgage Rights (SKMHT) as the initial binding of collateral before making a Deed of Granting Mortgage Rights (APHT). However, the regulation of the SKMHT period creates legal uncertainty, especially regarding Article 15 paragraphs (3) and (4) of the Mortgage Rights Law and banking technical provisions. The ambiguity of norms affects legal protection for creditors and debtors and may cause disputes in executing collateral.This research first analyzes the regulations on the SKMHT period and the vagueness of norms in MSME credit with land collateral. Second, it evaluates the reconstruction of ideal norms for SKMHT period settings to ensure legal certainty and protection in MSME credit practices.The research uses three approaches: the Statute Approach to examine SKMHT regulations, the Conceptual Approach to analyze legal doctrines, and the Comparative Approach to compare legal arrangements or court decisions from other countries.Three legal theories are applied: Legal Certainty Theory to resolve SKMHT term issues, Legal Protection Theory to analyze protection for creditors and debtors, and Responsibility Theory to review obligations of parties in MSME credit.The results show unclear norms cause legal uncertainty, and failure to convert SKMHT into APHT results in nullity. Therefore, reconstruction of SKMHT term norms in MSME credit with land collateral is required to ensure permanent legal force.